Superior vena cava syndrome in the CT scanning - Wróbel, Grzegorz (Journal of Medical Science, 2018)
The study concerns a 67-year-old woman with symptoms such as swelling of the face, neck and upper limbs; bruising in the head and neck region; conjunctival hyperemia; excessive filling of the jugular veins. The CT examination was performed using the SOMATOM Definition AS (Siemens) and analyzed with SYNGO Multi-Modality CT Workstation (Siemens). The study showed a tumoral mass (67 x 91 mm) located in the right upper lobe and adjacent to the mediastinum, simultaneously invades the superior vena cava and causes it to narrow completely.